ANALYTICAL ESTIMATE OF INFLUENCE OF THE LIMITED ANGULAR SIZE OF THE SUN IN A PROBLEM OF TWILIGHT SOUNDING OF THE ATMOSPHERE - Shakun, L. S. (Одеські астрономічні публікації, 2017)
The Sun has finite angular size. Therefore sunrays from different points of the solar disk have different trajectories in the atmosphere. General illumination produced by different parts of the solar disk differs even if the brightness of these parts is identical. Thus the illumination of some point in the atmosphere produced by the solar disk and the illumination of the same point produced by the Sun taken as a point source are different. It is shown that into a consideration angular size of the Sun doesn't influence the brightness of twilight sky. However, the brightness of some parts of twilight ray significantly increases. A new method of computing illumination of some point in the atmosphere is propound that takes into account angular size of the Sun.